2016
DOI: 10.1016/j.jacc.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Edge-to-Edge Treatment of Functional Tricuspid Regurgitation in an Ex Vivo Pulsatile Heart Model

Abstract: This experimental work demonstrated that the transcatheter edge-to-edge repair technique is a feasible approach for FTR. The study investigated this approach to develop a selective, specific structural intervention methodology for treating FTR, considering the several biomechanical factors that alter proper functionality of valvular substructures. These results can be used to guide the development of edge-to-edge repair techniques in treatment of FTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…Of these, 80 clips were positioned between the anterior and septal tricuspid leaflets, and 15 were placed between the posterior and septal tricuspid leaflets. The strategy of a clip placement into the antero‐septal commissure is supported by a pre‐clinical model of edge‐to‐edge TV repair which demonstrated a more effective TR reduction if the antero‐septal commissure was chosen in case of secondary TR . If a significant proportion of the TR jet originated in the postero‐septal commissure, clips were also placed into this position.…”
Section: Resultssupporting
confidence: 57%
“…Of these, 80 clips were positioned between the anterior and septal tricuspid leaflets, and 15 were placed between the posterior and septal tricuspid leaflets. The strategy of a clip placement into the antero‐septal commissure is supported by a pre‐clinical model of edge‐to‐edge TV repair which demonstrated a more effective TR reduction if the antero‐septal commissure was chosen in case of secondary TR . If a significant proportion of the TR jet originated in the postero‐septal commissure, clips were also placed into this position.…”
Section: Resultssupporting
confidence: 57%
“…Bench-test models have shown that the ideal location to place the clip to achieve the most pronounced reduction of TR in the presence of functional regurgitation is the anteroseptal commissure. 17 The use of the MitraClip system for the TV raised some specific issues due to the complexity of the TV itself, as the MitraClip system was designed specifically for the mitral valve. In the future, the technique must be refined and the device modified for dedicated…”
Section: The Millipede Systemmentioning
confidence: 99%
“…In an ex vivo pulsatile heart model study, grasping the septal and anterior leaflets allowed for the best post-procedural outcome. 34 Two-clip implantation involving the septalanterior and septal-posterior position also increased cardiac output.…”
Section: Image and Technique During Proceduresmentioning
confidence: 99%